Legal Effectiveness of Electronic Land Rights Transfer at Batam City Land Office - Suelyne Gracella Sitanggang (Universitas Negeri Semarang, 2026)
Land rights transfer in Indonesia has historically been hampered by bureaucratic inefficiency and lengthy processing times. In response, the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) has implemented an electronic land rights transfer system as part of broader e-government reform. This study evaluates the legal effectiveness of its implementation at the Batam City Land Office using an empirical legal research approach. Data were collected through in-depth interviews with Land Office officials, Land Deed Officials (PPAT), and service users, and analyzed through Soerjono Soekanto's five-factor theory of legal effectiveness. The findings show that the electronic system has significantly reduced processing time from 14–30 working days to a maximum of 5 working days and improved data transparency. However, full effectiveness has not been achieved, as three factors remain suboptimal: uneven staff digital capacity, Batam's distinctive dual-authority land tenure structure requiring BP Batam approval prior to ATR/BPN processing, and partial public resistance to electronic certificates. Regulatory harmonization and inter-institutional integration are recommended to address these constraints.